Human factors affecting ventilation in Australian classrooms during the COVID-19 pandemic: Toward insourcing occupants' proficiency in ventilation management - Snow, Stephen; Danam, Royce; Leardini, Paola; Glencross, Mashhuda; Beeson, Brett; Ottenhaus, Lisa-Mareike; Boden, Marie (Frontiers in Computer Science, 2022)
Underventilation in classrooms is associated with poorer academic performance and greater transmission risk of COVID-19. In a study involving data from CO2 logging in 67 classrooms in Brisbane, Australia, incorporating multiple seasons, it was found that more than half of the classrooms monitored experienced between 5-50 separate instances of CO2 concentrations exceeding 1,800 ppm, a level at which cognitive performance reductions have been recorded and which is considered high risk for COVID-19 transmission. The research identifies a number of human-related factors affecting ventilation in certain classrooms, including bolting windows closed for safety or minimising the potential for student interference, difficult to reach switches for exhaust fans and perceptions of the responsiveness of facilities management staff. Identifying Inbodied Interaction as a useful lens to enable users themselves to better identify and remedy instances of poor IAQ, the paper contributes: (1) Insight into the ventilation performance of Australian classrooms during the COVID pandemic; (2) Identification of human-factors contributing to the ventilation -and underventilation- of the rooms monitored; and (3) Suggestions for how to foster greater awareness of ventilation among classroom occupants and translate awareness into more active, informed and healthier ventilation behaviours from occupants, using principles of Inbodied Interaction.